Socio-Economic Dynamics of Communal Conflicts among Farmers in the Ogoja Agricultural Zone, Cross River State, Nigeria - Effiong, John Ben; Machu, Princely Odu (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study assessed the socioeconomic dynamics of communal conflicts among farmers in Ogoja Agricultural Zone. The specific objectives of the study were to; identify the socioeconomic characteristics of respondents in the study area and identify the various socioeconomic causes of communal conflicts in the study area such as; Encroachment into farmland by other people results to conflicts, Struggle for land in the community and neighboring communities generates conflicts, and Empowerment of youths with arms by politician easily triggers conflicts, among others. The study was conducted in Ogoja Agricultural Zone made up of Bekwarra, Obudu, Obanliku and Yala Local Government Areas. Two hundred and fifty (250) farmers were used for the study, data were obtained using structural questionnaire. The data were analyzed using descriptive statistics: frequency, percentage, mean and standard deviation. The result of the analysis showed that majority of the respondents were males constituting (70.40%), also majority were within the age brackets of 31 – 45 years. The study further revealed that a good number of the respondents were married (69.60%). A large proportion of the population had attained primary/secondary level of education being their highest educational standards. The socioeconomic caused of communal conflicts among farmers in the study area were; poor means of livelihood in the community = 4.26 (ranked 1st), criminal gang and cult activities = 4.42 (ranked 2nd), high level of illiteracy among young farmers = 4.15 (ranked 3rd). Based on the findings of this study, it is recommended that socioeconomic needs assessment should be carried out in conflict zones of Ogoja Agricultural belt with a view to solving some socioeconomic need of the people, such needs includes livelihood needs and literacy needs.